2017
DOI: 10.7554/elife.25480
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lithium treatment elicits its antimanic effects via BDNF-TrkB dependent synaptic downscaling

Abstract: Lithium is widely used as a treatment for Bipolar Disorder although the molecular mechanisms that underlie its therapeutic effects are under debate. In this study, we show brain-derived neurotrophic factor (BDNF) is required for the antimanic-like effects of lithium but not the antidepressant-like effects in mice. We performed whole cell patch clamp recordings of hippocampal neurons to determine the impact of lithium on synaptic transmission that may underlie the behavioral effects. Lithium produced a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 74 publications
0
39
0
Order By: Relevance
“…If so, changes in this adaptive regime may provide a fruitful approach when targeting network disruptions in chronic disease or psychopathology. Indeed, observations that adjustments in synaptic strength is a target for mood correcting drugs such as lithium 43 is consistent with this idea. It is also interesting to note that pharmacotherapy that corrects elevated CORT levels in diseases such as Cushing's, does not always resolve the behavioral symptomology.…”
Section: Discussionmentioning
confidence: 53%
“…If so, changes in this adaptive regime may provide a fruitful approach when targeting network disruptions in chronic disease or psychopathology. Indeed, observations that adjustments in synaptic strength is a target for mood correcting drugs such as lithium 43 is consistent with this idea. It is also interesting to note that pharmacotherapy that corrects elevated CORT levels in diseases such as Cushing's, does not always resolve the behavioral symptomology.…”
Section: Discussionmentioning
confidence: 53%
“…S3A,B). Further, although prolonged Li treatment (2 mM) is reported to reduce mEPSC amplitude in hippocampal neurons (25), here Li had no significant impact on basal postsynaptic ( Fig. S4 B,C) or neuronal ( Fig.…”
Section: Main Text 10mentioning
confidence: 53%
“…Recent studies had demonstrated that BDNF levels are lower in patients during active phases than BDNF levels in healthy controls [10][11][12][13][14]. Changes in serum BDNF levels in different phases and in following pharmacological interventions for acute affective phase in patients with bipolar disorders were addressed in several studies, but the results are still inconclusive [8,13,[15][16][17]. The serum BDNF protein level is reported to be a useful adjunctive tool for accurately diagnosing depressive bipolar disorder [18] and a marker for treatment response in bipolar disorder [11,14,19].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF levels measures in blood could reflect illness activity in the brain due to a positive correlation of BDNF levels between blood and cortex in mice, rats and pigs [7]. In addition, the tropomyosin receptor kinase (TrkB), a receptor of BDNF on cell membrane, is involved in bipolar disorder [8,9]. Several studies have adopted the BDNF as a molecular candidate for developing bipolar disorder [6,10].…”
Section: Discussionmentioning
confidence: 99%